Evidence for specificity in symbiont-conferred protection against parasitoids - McLean, Ailsa H. C. (Proc Biol Sci, 2015)
Many insects harbour facultative symbiotic bacteria, some of which have been shown to provide resistance against natural enemies. One of the best-known protective symbionts is Hamiltonella defensa, which in pea aphid (Acyrthosiphon pisum) confers resistance against attack by parasitoid wasps in the genus Aphidius (Braconidae). We asked (i) whether this symbiont also confers protection against a phylogenetically distant group of parasitoids (Aphelinidae) and (ii) whether there are consistent differences in the effects of bacteria found in pea aphid biotypes adapted to different host plants. We found that some H. defensa strains do provide protection against an aphelinid parasitoid Aphelinus abdominalis. Hamiltonella defensa from the Lotus biotype provided high resistance to A. abdominalis and moderate to low resistance to Aphidius ervi, while the reverse was seen from Medicago biotype isolates. Aphids from Ononis showed no evidence of symbiont-mediated protection against either wasp species and were relatively vulnerable to both. Our results may reflect the different selection pressures exerted by the parasitoid community on aphids feeding on different host plants, and could help explain the maintenance of genetic diversity in bacterial symbionts.